Philosophy of science matters : the philosophy of Peter Achinstein - Morgan, Gregory J. (New York ; OXford : Oxford University Press, 2011)
Devoted to Peter Achinstein's work in the philosophy of science, this work features twenty distinguished philosophers, including four Lakatos award winners. They address various aspects of Achinstein's influential views on the nature of scientific evidence, scientific explanation, and scientific realism.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Achinstein, Peter; Science -- Philosophy